Transitions from child and adolescent mental health services (CAMHS) for young people with social care needs in Wales - Roberts, Louisa M (International Journal of Population Data Science, 2025)
Childhood to adulthood transitions are often characterised by instability and increased support needs, particularly for young people involved with mental health and social care services. This study maps differing mental health service pathways experienced by young people in Wales, highlighting those at risk of ‘falling through the net’ of support. This study was a longitudinal cohort analysis of SAIL Databank health and social care data of young people aged 16-to-21. Descriptive statistics were used to map mental health diagnoses, and sociodemographic characteristics including social care status, gender, ethnicity, area level deprivation and health board area, for young people who have transitioned from CAMHS to adult mental health services (AMHS) compared with those who have not transitioned by age 21. Logistic regression modelling and sequence analyses were used to further explore how these factors may interact and influence how young people access ongoing support in AMHS in Wales. The results showed young people looked after or receiving social work support at home in Wales were over-represented in CAMHS. However, at transition age the access to AMHS for these vulnerable groups greatly reduced, becoming broadly aligned with the general population. Higher proportions of young people involved with social services had mental health related diagnosis codes present in their health records, but the likelihood of transition to AMHS when diagnosis codes are present appeared lower than for young people with the same diagnosis codes but no social services involvement. Patterns of mental health service transition also varied by gender, ethnicity, area level deprivation and health board, and those patterns were different between cohorts of young people involved with, or not involved with, social care services. Given known increased support needs for young people involved with social care, their reduced representation in mental health services at transition is of great concern. Policy, practice and research implications are offered, to consider how best to support vulnerable young people in Wales as they transition from childhood to adulthood.